Lab-scale engineered hydrochar production and techno-economic scaling-up analysis - Kannan, N.; Rodriguez-Narvaez, M.; Jerome, R.; Bandala, E.R; Ashantha, G. (Elsevier, 2024)
Despite the extensive use of engineered hydrochar (EHC) for contaminants adsorption in water, little is known about the scaling-up of EHC production which has kept the technology at a low readiness level (TRL). Full-scale EHC production was simulated to help bridge this knowledge gap. A systematic analysis was performed where EHC was produced from rice straw using hydrothermal carbonization (HTC) at 200 ◦C with iron addition. A techno-economic evaluation model was employed to simulate the production process and to estimate energy requirements, configuration, and cost scenarios for the HTC process. The minimum selling price (MSP) analysis of the engineered hydrochar was found to be almost half compared to the market price for other similar sorbents ($ 76/t vs. $136/t) suggesting that EHC production is feasible for scaling up. Finally, as a trial, the resulting material was tested for its efficacy in the adsorption of an anionic organic contaminant (e.g., Congo Red, C32H22N6Na2O6S2) in water to identify its potential for water treatment. Experimental results showed that EHC adsorbed > 95% CR suggesting significant adsorption capability and feasibility for production scale-up.
Keywords: Hydrochar; Engineered hydrochar; Adsorption; Congo red; Techno-economic analysis